La nascita e l’origine della mente: la luce e il tempo vissuto - Gatti, Maria Gabriella (Il sogno della farfalla, 2016)
The author demonstrates how the most recent biological and neonatalogical research integrate with Massimo Fagioli’s Birth Theory. At birth, when the light makes contact with cerebral matter, a real and proper shift takes place: from the foetus which has only a biological specificity void of any mental activity, to the newborn whose “lived” body is at the origin of psychic processes.